THE IMPACT OF TEACHER QUESTIONING ON CREATING INTERACTION IN EFL CLASSROOM: A DISCOURSE ANALYSIS - Arif Rahman (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2023)
Rastiani. 2019. The Impact of Teacher Questioning on Creating Interaction in EFL: A Discourse Analysis (A Descriptive Qualitative Research at SMP Mataram). This study examines the effect of questions on fostering interactions in English as a Foreign Language (EFL) classroom. It also seeks to determine the characteristics of questions that encourage increased classroom interaction. Data were collected through EFL classroom video recordings that were analyzed using the Discourse Analysis technique. Participants in this study were students of SMPN Mataram. First, participating classes are videotaped and the data collected is transcribed. The questions asked in each class are then divided into two groups: questions that are considered to increase class interaction and questions that fail to create class interaction. Finally, the defining features of each group of questions are determined. The results show that the impact of teacher questions in creating classroom interaction is effective. In other words, several types of questions significantly increase class interaction.